The Development of Guided Inquiry-Based Basic Accounting Module - Oktasari Oktasari; Siswandari Siswandari; Djoko Santosa (Budapest International Research and Critics University, 2019)
This research focused on how the development of basic accounting module materials based on guided inquiry that is appropriate for vocational high school based on needs analysis is. The research procedure was 4D development model consisting of Define, Design, Develop, and Disseminate. Population of this research was vocational students with 64 students as the sample through a purposive sampling technique. Technique of data collection used was questionnaire and interview. The data collected was analyzed by using descriptive statistic analysis. The results showed that the developed teaching material of basic accounting module based on guided inquiry was feasible to use. The analysis results showed that: (1) validation from media experts derived an average percentage of 98.13% included in